Ride the wavelet: A multiscale analysis of genomic contexts flanking small insertions and deletions - Kvikstad, Erika M.; Chiaromonte, Francesca; Makova, Kateryna D. (Genome Research, 2009)
Recent studies have revealed that insertions and deletions (indels) are more different in their formation than previously assumed. What remains enigmatic is how the local DNA sequence context contributes to these differences. To investigate the relative impact of various molecular mechanisms to indel formation, we analyzed sequence contexts of indels in the non protein- or RNA-coding, nonrepetitive (NCNR) portion of the human genome. We considered small (≤30-bp) indels occurring in the human lineage since its divergence from chimpanzee and used wavelet techniques to study, simultaneously for multiple scales, the spatial patterns of short sequence motifs associated with indel mutagenesis. In particular, we focused on motifs associated with DNA polymerase activity, topoisomerase cleavage, double-strand breaks (DSBs), and their repair. We came to the following conclusions. First, many motifs are characterized by unique enrichment profiles in the vicinity of indels vs. indel-free portions of the genome, verifying the importance of sequence context in indel mutagenesis. Second, only limited similarity in motif frequency profiles is evident flanking insertions vs. deletions, confirming differences in their mutagenesis. Third, substantial similarity in frequency profiles exists between pairs of individual motifs flanking insertions (and separately deletions), suggesting “cooperation” among motifs, and thus molecular mechanisms, during indel formation. Fourth, the wavelet analyses demonstrate that all these patterns are highly dependent on scale (the size of an interval considered). Finally, our results depict a model of indel mutagenesis comprising both replication and recombination (via repair of paused replication forks and site-specific recombination).
10.1101/gr.088922.108